Dependence in the elderly - Çavuşoğlu, Çağatay; Demirkol, Mehmet Emin (Journal of Dependence, 2018)
Disorders related to substance use in elderly individuals are one of the most noticeable problems in recent years. In a study about substance use conducted in 2015, 17.3% of the approximately 1,500,000 patients who applied for treatment due to substance use disorders were found to be 50 years of age or older. Many causes, such as the combination of many chronic diseases in elderly people, the use of multiple drugs, changes in kidney and liver functions, significantly increase the deleterious effects of substance use and make the problem much more complicated. Although there are many screening tests to detect substance-related disorders in young individuals, many of the same tests are not valid for elderly individuals. Alcohol is currently the most commonly used substance, benzodiazepine, opiate group drugs, marijuana use is increasing day by day. Treatment is also an important issue and needs to be assessed carefully as well as the detection of a problem in elderly individuals. In a study it was predicted that treatment related to substance use in elderly individuals would increase by 250% and affect 4.4 million people by 2020. Therefore, substance-related disorders in elderly individuals should be investigated in detail and new researches on this subject are needed.